ChemInform Abstract: [1, 2, 5]Selenadiazolo[3, 4‐b]pyrazines: Synthesis from 3, 4‐Diamino‐1, 2, 5‐selenadiazole and Generation of Persistent Radical Anions. Issue 1 (17th December 2015) - Rakitin, Oleg A.; et al.,
Abstract: Novel selenadiazolediamine (II) is prepared and used in the synthesis of selenadiazolopyrazines by Koerner—Hinsberg cyclocondensation with 1, 2‐dicarbonyls.